Prodromus of a fern flora for Bolivia. I. General introduction and key to families - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2017)
We introduce the concept of a prodromus for a flora to the ferns and lycophytes of Bolivia, describe the natural setting of Bolivia (topography, climate, vegetation), briefly review the history of pteridological knowledge in the country, present a taxonomic synopsis as well as a key to the fern and lycophyte families of Bolivia, and provide a list of all fern and lycophyte names with Bolivian type material. A new combination is proposed for Polyphlebium herzogii (Rosenst.) A.R.Sm. & Kessler.